DOGMA JAMINAN KESELAMATAN DALAM GEREJA KHATOLIK DAN LUTHERAN BERADASARKAN DOKUMEN JOINT DECLARATION ON THE DOCTRINE OF JUSTIFICATION TAHUN 1999 - Paulinus Tibo; Oddy Adventa Tarigan; Ramli Tua Simarmata (Pastoralia, 2026)
This study aims to analyze and compare the understanding of assurance of salvation in the dogma of the Roman Catholic Church and the tradition of Martin Luther that gave birth to the Lutheran Church. In the Catholic Church, assurance of salvation is understood as a process that takes place through God's grace, sanctification, and the involvement of the faithful in the sacraments and moral life. Meanwhile, the Lutheran tradition emphasizes that salvation is received entirely as a gift from God (sola gratia), through faith (sola fide), and based on the authority of Scripture (sola scriptura), with Christ as the only basis of salvation (solus Christus). The research method used a literature study with a dogmatic-historical approach, examining the documents of the Council of Trent, the Augsburg Confession, Luther's writings, and the magisterial documents of the Catholic Church, including the Joint Declaration on the Doctrine of Justification (JDDJ). The research indicates that the JDDJ is an important milestone in modern ecumenism because it affirms the basic agreement between the two traditions: humans are justified solely by grace through faith in Christ, while true faith always produces love and renewal of life. The results of the study show that the main difference lies in emphasis: the Catholic Church highlights the continuity of grace lived out in the sacraments and morality, while Lutherans emphasize the certainty of salvation received through faith that bears the fruit of love. Nevertheless, both agree that salvation is entirely the work of God through Christ. This research is expected to enrich soteriological understanding and strengthen fraternal dialogue between Christian denominations so that the experience of faith is increasingly rooted in God's saving grace.